State of stress and crustal fluid migration related to west-dipping structures in the slab-forearc system in the northern Chilean subduction zone. Issue 3 (9th December 2016) - Salazar, P.; Kummerow, J.; Wigger, P.; Shapiro, S.; Asch, G.
Abstract: Previous studies in the forearc of the northern Chilean subduction zone have identified important tectonic features in the upper crust. As a result of these works, the West Fissure Fault System (WFFS) has recently been imaged using microseismic events. The WFFS is the westward-dipping, sharp lower boundary of the northern Chilean forearc and is geometrically opposed to subduction of the Nazca plate. The present article builds on this previous work and is novel in that it characterizes this structure's stress distribution using focal mechanisms and stress tensor analysis. The results of the stress tensor analysis show that the state of stress in the WFFS is related to its strike-slip tectonic context and likely represents a manifestation of local forces associated with the highest areas in the Andes. Two seismic clusters have also been identified; these clusters may be associated with a blind branch of the WFFS. We studied these clusters in order to determine their sources and possible connection with fluid migration across the upper plate. We observed that the two clusters differ from one another in some regards. The central cluster has characteristics consistent with an earthquake swarm with two clearly identifiable phases. Conversely, the SW cluster has a clear main shock associated with it, and it can be separated into two subclusters (A and A ΄ ). In contrast, similarities among the two clusters suggest that the clusters may have a common origin. The b -values for both clusters are characteristic of tectonic plate boundaries. The spatial spreading, which is approximately confined to one plane, reflects progressive growth of the main fracture underlying the swarm and subcluster A. We also find that earthquakes themselves trigger aftershocks near the borders of their rupture areas. In addition, the spatio-temporal migration of hypocentres, as well as their spatial correlation with areas that are interpreted to be fluid migration zones, suggest that there is a close relationship between fluid movement and the earthquake sources associated with the swarm and subcluster A. These observations point to stick-slip behaviour of the rupture propagation, which can be explained by earthquake-induced stress transfer and fluid flow in a fluid-permeated, critically loaded fault zone.